Prevalence of monoclonal gammopathy of undetermined significance in Shenzhen, China - Anping Xu; Tong Guo; Shuping Zhang; Houlong Luo; Mengxue Shen; Yinghui Ye; Ling Ji (Hematology)
Background Data on the prevalence of monoclonal gammopathy of undetermined significance (MGUS) in China are very limited. Our aim was to determine the prevalence and clinical characteristics of MGUS in a large Chinese population.Methods This study included 49,220 healthy people who received serum immunofixation electrophoresis (sIFE) and serum protein electrophoresis (SPE) tests. Serum free light chain ratio, immunoglobulin quantification, and other clinically correlates of MGUS were performed for all patients with M-protein.Results A total of 576 MGUS patients were identified by sIFE, with a median age of 58 years and an overall prevalence of 1.17% (95% CI, 1.08–1.27). Among those aged 50 years and older, the prevalence of MGUS was 2.26% (95% CI, 2.04–2.50). The prevalence of MGUS was significantly higher in males than in females (P < 0.05). The median concentration of M-protein was 3.1 g/L, ranging from 0.5 g/L to 25.1 g/L. The M-protein type was IgG in 55.4% of MGUS patients, followed by IgA (31.1%), IgM (9.5%), IgD (0.5%), biclonal (2.3%), and light chain (1.2%). Abnormalities in SPE, FLC ratios, and immunoglobulin levels were observed in 78.3%, 31.1%, and 38.4% of MGUS patients, respectively.Conclusions The prevalence of MGUS is substantially lower in southern China than in whites and blacks.